Dense understory and absence of capuchin monkeys (Sapajus xanthosternos) predict higher density of common marmosets (Callithrix jacchus) in the Brazilian Northeast. Issue 4 (18th November 2014) - Hilário, Renato R.; Ferrari, Stephen F.
Abstract : Understanding the effects of habitat structure and other environmental variables on the density of a species can help define its habitat preferences and key ecological determinants of population parameters. The present study evaluated the effects of fragment size, the presence of a key predator/competitor, the yellow‐breasted capuchin ( Sapajus xanthosternos ), primary productivity, the abundance of bromeliads, and habitat structure on the population density of the common marmoset ( Callithrix jacchus ). A total of 21 fragments were surveyed within a 350‐km long zone of coastal Atlantic Forest representing the southern extreme of the distribution of the species in the Brazilian Northeast. An index of marmoset density was generated for each site based on playback surveys. The relationship between the density of marmosets and a set of parameters was evaluated by multiple regression. A Principal Components Analysis (PCA) condensed the five variables of habitat structure into two principal components, which contained 85% of their combined variation. The model that best explained the density of marmosets ( R 2  = 59.1) contained the second PCA component and the presence/absence of capuchins. The analysis indicated that the marmosets prefer forests with denser understory, whether or not they are secondary habitats. The negative effect of the presence of capuchins may be related to predation pressure. The results of this study indicate that multiple‐site studies may provide important insights into the habitat preferences of primate species and the factors that affect their population density. Am. J. Primatol. 77:425–433, 2015. © 2014 Wiley Periodicals, Inc.